The Novel Heuristic for Data Transmission Dynamic Scheduling Problems. (16th December 2013) - Xu, Hao; Zhao, Yue; Xing, Li-Ning; Zhou, You
Abstract : The data transmission dynamic scheduling is a process that allocates the ground stations and available time windows to the data transmission tasks dynamically for improving the resource utilization. A novel heuristic is proposed to solve the data transmission dynamic scheduling problem. The characteristic of this heuristic is the dynamic hybridization of simple rules. Experimental results suggest that the proposed algorithm is correct, feasible, and available. The dynamic hybridization of simple rules can largely improve the efficiency of scheduling.